Desprecarização do trabalho no sus: um estudo sobre o plano de cargos, carreiras e salários do sus, na perspectiva dos trabalhadores e representantes sindicais no município de Guarulhos, Região Metropolitana de São Paulo - Rizzo, Tamiris Pereira [UNIFESP] (2014)
This qualitative study aimed at apprehending, from the perspective of the municipal workers at SUS Guarulhos and union representation, the role of the Post, Career and Salary Plan (PCCS) as an instrument of improvement of work relations at SUS; as well as identifying the actions of these actors in the construction of this proposal. Regarding the method, the document analysis was held from the minutes of the Health City Council meetings and union bulletins, as well as the analysis of interviews with managers and union representatives beyond the focal group of workers of the health network, using the content analysis tool. With regard to the results, it was observed that the PCCS has strong administrative and technical bias and suffered budget constraints that have compromised their application according to law. The plan represented an important, though limited, tool to promote working relations that through an open tender would ensure labor and social rights. Its main limitation is the fact that its scope has met just 68% of workers in the sector, and that its implementation and possible expansion followed coexisting with the municipal administration of direct promotion of managed services contracts and human resources contracting through public non-state partnerships. The CLT contract regime also limits the stability of formal workers. There was no role of workers and their unions in the construction of the proposal. As a conclusion, one can say that improvement of labor relations at SUS goes beyond the limits of the PCCS and the observation of bonds that ensure labor and social rights. One should also consider confronting the obstacles brought by the State Administrative Reform in the health sector in pursuit of fulfillment of the main paradigms of Health Reform at the macro level structure and at the level of labor relations with the loss of the meaning of work, as shown by the theoretical framework adopted in this study.